RECQ1 Promotes Stress Resistance and DNA Replication Progression Through PARP1 Signaling Pathway in Glioblastoma - Zhang, Jing; Lian, Hao; Chen, Kui; Pang, Ying; Chen, Mu; Huang, Bingsong; Zhu, Lei; Xu, Siyi; Liu, Min; Zhong, Chunlong (Frontiers in Cell and Developmental Biology, 2021)
Glioblastoma (GBM) is the most common aggressive primary malignant brain tumor, and patients with GBM have a median survival of 20 months. Clinical therapy resistance is a challenging barrier to overcome. Tumor genome stability maintenance during DNA replication, especially the ability to respond to replication stress, is highly correlated with drug resistance. Recently, we identified a protective role for RECQ1 under replication stress conditions. RECQ1 acts at replication forks, binds PCNA, inhibits single-strand DNA formation and nascent strand degradation in GBM cells. It is associated with the function of the PARP1 protein, promoting PARP1 recruitment to replication sites. RECQ1 is essential for DNA replication fork protection and tumor cell proliferation under replication stress conditions, and as a target of RECQ1, PARP1 effectively protects and restarts stalled replication forks, providing new insights into genomic stability maintenance and replication stress resistance. These findings indicate that tumor genome stability targeting RECQ1-PARP1 signaling may be a promising therapeutic intervention to overcome therapy resistance in GBM.